Analytics, innovation, and excellence-driven enterprise sustainability - Carayannis, Elias G.; Sindakis, Stavros, 1981- (Palgrave Macmillan, 2017)
This book offers a unique view of how innovativeness and competitiveness improve when organizations establish alliances with partners who have strong capabilities and broad social capital, allowing them to create value and growth as well as technological knowledge and legitimacy through new knowledge resources. Organizational intelligence integrates the technology variable into production and business systems, establishing a basis to advance decision-making processes. When strategically integrated, these factors have the power to promote enterprise resilience, robustness, and sustainability. This book provides a unique perspective on how knowledge, information, and data analytics create opportunities and challenges for sustainable enterprise excellence. It also shows how the value of digital technology at both personal and industrial levels leads to new opportunities for creating experiences, processes, and organizational forms that fundamentally reshape organizations.- Resumé vydavatel
Keywords: business intelligence; analýza dat; udržitelný rozvoj; data analysis; sustainable development; elektronické knihy; sborníky; electronic books; papers of several authors